Regulatory capital and risk of Indian banks: a simultaneous equation approach. Issue 2 (5th May 2015) - Maji, Santi Gopal; De, Utpal Kumar
Abstract : Purpose: – This paper aims to examine the association between regulatory capital and risk of Indian commercial banks and the impacts of other relevant variables on them. Design/methodology/approach: – The study is based on a secondary data set on Indian commercial banks collected from "Capitaline Plus" corporate database and annual reports of the respective banks. Total 41 major Indian banks (21 public and 20 private sector banks) are considered in this study. Here absolute values of capital and risk are used as dependent variables along with some relevant bank specific explanatory variables in a system of a two-equation model. Based on the nature of interrelationship and identifiability of the equations, three-stage least squares (3SLS) technique is used to estimate the relationship. Findings: – Risk and capital of Indian commercial banks are inversely associated. The influence of profitability on both capital and risk is significantly positive. Moreover, human capital efficiency is negatively associated with the undertaking of risk by the banks. In this respect, Indian private sector banks are found to be more efficient in utilizing human capital for reducing credit risk. Originality/value: – It is the first comparative study in India examining the relationship between capital and risk of Indian public and private sector commercial banks covering both Basel I and II periods. Further, the role of human resource in managing risk is considered as a relevant variable in this study.